VD_FINDINFO Jug / 2012 / 326 vom 4. Dezember 2012 - VD Tribunal cantonal (2012)
EXEQUATURCONSUL, VISITE, RELATIONS PERSONNELLES, DÉCISION ÉTRANGÈRE | 10 par. 1 let. a CE 80, 10 par. 1 let. d CE 80, 14 CE 80, 7 CE 80